2019
DOI: 10.3390/molecules24102017
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Approaches in Tackling Cardiovascular Diseases

Abstract: Cardiovascular diseases have continued to remain a leading cause of mortality and morbidity worldwide. Poor proliferation capability of adult cardiomyocytes disables the heart from regenerating new myocardium after a myocardial ischaemia event and therefore weakens the heart in the long term, which may result in heart failure and death. Delivery of cardioprotective therapeutics soon after the event can help to protect the heart from further cell death and improve cardiac function, but delivery methods and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Nanomaterials have been explored as drug delivery carriers for localized and controlled delivery of drugs to the target site. In cardiovascular medicine, conventional drugs or novel synthetic compounds are delivered to reduce atherosclerotic lesion formation, promote angiogenesis in ischemic tissues and improve the remodelling process in the damaged organs [ [68] , [69] , [70] ]. In the emerging area of nanotechnology, carbon allotropes are considered as one of the cardinal classes, which have gained significant attention in drug delivery applications [ 71 , 72 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…Nanomaterials have been explored as drug delivery carriers for localized and controlled delivery of drugs to the target site. In cardiovascular medicine, conventional drugs or novel synthetic compounds are delivered to reduce atherosclerotic lesion formation, promote angiogenesis in ischemic tissues and improve the remodelling process in the damaged organs [ [68] , [69] , [70] ]. In the emerging area of nanotechnology, carbon allotropes are considered as one of the cardinal classes, which have gained significant attention in drug delivery applications [ 71 , 72 ].…”
Section: Application Of Cnms In Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…Cardiovascular diseases cause millions of deaths around the world [ 18 ]. Various treatments have improved the survival rate of patients with heart diseases but none of them has achieved complete cardiac regeneration, especially for patients after cardiac infarction [ 107 ].…”
Section: Applications Of Nanotechnology In Healthcare Sectorsmentioning
confidence: 99%
“…Nanotechnology products have become increasingly useful in healthcare and have led to the advent of novel nanosystems for the diagnosis, imaging, and treatment of various diseases, such as cancer, as well as cardiovascular, ocular, and central nervous system-related diseases [ 16 , 17 , 18 ]. Nanomaterials integrate well into biomedical devices because most biological systems are also nanosized [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been applied in multiple fields, including drug delivery, bioengineering, diagnostics, and sensing ( Chacko et al, 2012 ). The emergence of nano-gels has greatly enriched and promoted the application of polymer NMs in treating ASCVD ( Chen et al, 2013 ; Grimaudo et al, 2019 ; Prajnamitra et al, 2019 ). For example, Tang et al devised thermosensitive nano-gels encapsulating therapeutic cells to treat MI through intramyocardial injection and showed that the nano-gels protect transplanted cells from attack by immune cells and also provide an environment conducive to their survival, indicating great value and potential for clinical use ( Tang et al, 2017 ).…”
Section: Nanomedicines For Drug Deliverymentioning
confidence: 99%